Milk Consumption after Age 9 Years Does Not Predict Age at Menarche(1)(2)(3) - Carwile, Jenny L (J Nutr, 2015)
Background: Regular milk consumption during childhood and adolescence is recommended for bone health. However, milk consumption increases circulating insulin-like growth factor I concentrations, and may also accelerate puberty. Objective: We prospectively investigated the association between milk consumption and age at menarche in the Growing Up Today Study. Methods: Study participants were 5583 US girls who were premenarcheal and ages 9–14 y in 1996. Girls were followed through 2001, at which time 97% of noncensored participants had reported menarche. Frequency of milk and meat consumption was calculated with the use of annual youth/adolescent food frequency questionnaires from 1996–1998. Intake of related nutrients was also measured. Age at menarche was self-reported annually through 2001. Results: During follow-up, 5227 girls attained menarche over 10,555 accrued person-years. In models adjusted for dietary and sociodemographic predictors of menarche, frequency of milk consumption did not predict age at onset of menarche (for >3 glasses of milk/d vs. 1.1–4 glasses/wk, HR: 0.93; 95% CI: 0.83, 1.04). After additional adjustment for body size, premenarcheal girls consuming >3 glasses of milk daily were 13% less likely (95% CI: −3%, −23%; P-trend: <0.01) to attain menarche in the next month relative to those consuming 1.1–4 glasses/wk. Neither total meat nor red meat consumption was associated with age at menarche. Conclusions: Our findings suggest that regular consumption of milk in girls aged ≥9 y is unlikely to substantially affect age at onset of menarche. Studies assessing associations between diet in early childhood and pubertal timing may be more illuminating.